Collection of research students in statistic siri 3 / Nur Intan Syafinaz Ahmad and Aishah Mahat - Ahmad, Nur Intan Syafinaz; Mahat, Aishah (UiTM Cawangan Johor Kampus Pasir Gudang, 2023)
This e-book Collection of Research Study in Statistics SIRI 3 aimed to aid students in topic Statistics. Targeted users for this e-book is for students who take course Statistics in university. There are many statistics reference books available, but we decided to create one book with very brief supporting documents so that students could help enhance their presentation and report writing skills. It is hoped that this book will not only assist students in learning, but will also aid them in excel at the foundation level of Statistics. Thank you to all those who contributed in making the publication of this book a reality